Small-Scale and Time Shortening Sample Preparation Procedure to Quantify Astaxanthin, Canthaxanthin, and \(β\)-Apo-8’-Carotenoic Acid Ethyl Ester in Hen’s Egg Yolk - N. Furusawa (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
Eggs are a very important and basic food because they are highly nutritious, cheap, and readily available. To ensure the safety of eggs, it is important to enhance their residual monitoring. The present chapter described a simple, small-scale, and time shortening procedure of sample preparation followed by high-performance liquid chromatography (HPLC) coupled photodiode array (PDA) detector for simultaneous quantification of astaxanthin (AX), canthaxanthin (CX), and \(β\)-apo-8’-carotenoic acid ethyl ester (ACAEE) in hen’s egg yolk. The HPLC-PDA was carried out with an isocratic mobile phase on a C18 column. Within 30 minutes, analytes were removed from the sample with a handheld ultrasonic homogenizer, purified with MonoSpin®-SI, a centrifugal monolithic silica spin mini-column, and measured. The suggested approach yielded average recoveries of 70.5-101.1 percent for the three analytes, with relative standard deviations \(\)5.0%. The quantitation limits were 0.3 \(μ\)g g-1 for AX, 0.5 \(μ\)g g-1 for CX, and 1.0 \(μ\)g g-1 for ACAEE, respectively. The total time required for the analysis of a single sample was <30 min.